Research Methodology of the City’s History of Everyday Life - Bukanova R. G., Kazhenova G. T., Abdykulova G., Mussabalina G. T., (Opción, 2019)
Analysis of the works of Russian and Western authors gave an opportunity to identify the authors’ opinions on the methodology of the history of everyday life. Authors study the application of an interdisciplinary approach in studying the history of everyday life, the advantages and minuses of other approaches. As a result, the history of everyday life cannot be structured without the use of problem-chronological, historical and typological methods. The authors came to the conclusion that the history of everyday life is not an independent scientific field with its own methodological apparatus.